Acute flaccid paralysis in South African children: Causes, respiratory complications and neurological outcome. (28th September 2017) - van der Pijl, Jolanda; Wilmshurst, Jo M; van Dijk, Monique; Argent, Andrew; Booth, Jane; Zampoli, Marco
Abstract : Aim: To describe the causes, clinical presentation and neurological outcome of acute flaccid paralysis in children. Methods: A retrospective study in a tertiary paediatric hospital in South Africa. Data on clinical presentation, respiratory complications and long‐term neurological outcomes of children presenting with acute flaccid paralysis were collected. Logistic regression analysis was applied to determine predictors for the need of mechanical ventilation. Results: The study included 119 patients, 99 of whom had Guillain‐Barré syndrome (GBS); 47 patients (39.5%) required mechanical ventilation. Backward logistic regression analysis revealed that bulbar dysfunction ( P < 0.001), autonomic dysfunction ( P = 0.003) and upper limb paralysis ( P = 0.038) significantly predicted the need for mechanical ventilation. EuroQol‐5D scores of self‐care problems and usual activities after discharge significantly declined over time. Conclusions: In this large series from Africa, GBS was the main cause of acute flaccid paralysis in children and was associated with significant morbidity. Other causes of acute flaccid paralysis mimicking GBS were not uncommon and should be excluded in this setting.